Helena Modrzejewska deklamuje .......... 39 - Maresz, Barbara („Szalony, kto nie chce wyżej, jeżeli może”: Studia i materiały do badań nad życiem i twórczością Heleny Modrzejewskiej, 2025)
HELENA MODRZEJEWSKA DECLAIMS…Declamation played a significant role in the artistic career of Helena Modrzejewska, although it is relatively under-recognized and seldom described. The text gathers scattered information about all Polish performances of the declamatory actress, primarily during charity concerts, matinees and musical and theatrical evenings. Modrzejewska delivered at least 100 public performances in Poland, in redoubt halls, resorts, town halls, hotels and salons. She recited in Cracow, Lviv, Warsaw, Poznan, Tarnów, Szczawnica and Zakopane. Her repertoire included works by notable poets such as Teofil Lenartowicz (Wiochna), Kornel Ujejski (Hagar na puszczy), Adam Mickiewicz, Zygmunt Krasiński, Adam Asnyk, and others. She was, next to Jan Królikowski, the most outstanding declamatory artist of the epoch of stars. The article is supplemented with a repertoire of Modrzejewska’s Polish declamatory performances from 1867 to 1902.